2017
DOI: 10.1177/2332649217717741
|View full text |Cite
|
Sign up to set email alerts
|

Trust in the Bayou City: Do Racial Segregation and Discrimination Matter for Generalized Trust?

Abstract: The key role that generalized trust plays in social capital formation is well documented, but its determinants are not well understood. Many studies suggest that racially and ethnically diverse areas have lower generalized trust than more homogeneous areas, but evidence regarding the impact of the spatial arrangement of racial and ethnic groups is not conclusive. Further, while scholars theorize that discrimination may play a role in racial trust gaps, no study has empirically supported this linkage. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
0
15
1
Order By: Relevance
“…My analysis of known-groups validity provides preliminary and tentative answers. At the individual-level, it may be worthwhile to reconsider prior findings linking generalized trust to age (Clark and Eisenstein 2013;Putnam 2000;Robinson and Jackson 2001), race-ethnicity (Douds and Wu 2018;Evangelist 2021;Wilkes 2011), and dispositional optimism (Andersson 2012;Uslaner 2002). The state-level analysis suggests that previous estimates of ethnic heterogeneity (Alesina and La Ferrara 2002;Marschall and Stolle 2004;Putnam 2007;Uslaner 2012) and intentional homicide (Putnam 2000;Messner et al 2004;Rosenfeld et al 2007) might be upwardly biased.…”
Section: Summary Of Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…My analysis of known-groups validity provides preliminary and tentative answers. At the individual-level, it may be worthwhile to reconsider prior findings linking generalized trust to age (Clark and Eisenstein 2013;Putnam 2000;Robinson and Jackson 2001), race-ethnicity (Douds and Wu 2018;Evangelist 2021;Wilkes 2011), and dispositional optimism (Andersson 2012;Uslaner 2002). The state-level analysis suggests that previous estimates of ethnic heterogeneity (Alesina and La Ferrara 2002;Marschall and Stolle 2004;Putnam 2007;Uslaner 2012) and intentional homicide (Putnam 2000;Messner et al 2004;Rosenfeld et al 2007) might be upwardly biased.…”
Section: Summary Of Resultsmentioning
confidence: 97%
“…All other key individual-level variables are statistically unrelated to SFT-60 and IST-6. This is a significant finding, which shows that generalized trust, measured as SFT-60 and IST-6, does not exhibit differences by age (Clark and Eisenstein 2013;Putnam 2000;Robinson and Jackson 2001), gender (Alesina and La Ferrara 2002;Mewes 2014), race and ethnicity (Douds and Wu 2018;Evangelist 2021;Wilkes 2011), and socioeconomic status (e.g., education; Oskarsson et al 2017).…”
Section: Known-groups Validitymentioning
confidence: 83%
See 1 more Smart Citation
“…34 Although one study found that generalized trust is sometimes higher among people who live in racially segregated communities because people trust others in their community with whom they have much in common, the same study also found that people with a close personal friend from a different racial or ethnic background are more likely to report having higher generalized trust. 35 A society with segregated neighborhoods, schools, and workplaces reduces the odds of developing close personal friendships with people from different backgrounds.…”
Section: We Need Institutions That Encourage People To Think In Termsmentioning
confidence: 99%
“…The few studies that have used a mediation approach to considering explain ethnic differences in trust (e.g., see De Vroome et al, 2013 ; Wilkes and Wu, 2018 ) do not have a measure of discrimination and do not use formal mediation analysis. Similarly, while Douds and Wu ( 2018 ) include models that look at how discrimination mediates the Black-White and Hispanic-White gaps in trust in Louisiana, they do not use a formal test of mediation. The strength of the mediation framework is that not only does it allow us to assess whether discrimination explains some of the impact of immigrant status on trust but also, as we highlight below, the relative importance of discrimination in explaining trust for different immigrant and native born and racialized groups.…”
Section: Discrimination As a Mediatormentioning
confidence: 99%